Safety of dexmedetomidine in the cardiac intensive care unit. Issue 4 (28th August 2020) - Adie, Sarah K; Farina, Nicholas; Abdul-Aziz, Ahmad A; Lee, Ran; Thomas, Michael P; Konerman, Matthew C
Abstract: Aims: Dexmedetomidine is one of the sedative agents recommended by the Society of Critical Care Medicine as a preferred option over benzodiazepines in critically ill, mechanically ventilated patients. Little data exists describing sedation in the cardiac intensive care unit (CICU). The purpose of this study was to determine the prevalence of adverse events in CICU patients treated with dexmedetomidine. Methods and results: This was a retrospective cohort analysis of patients >18 years old admitted to the University of Michigan CICU from June 2014 to October 2019 who received dexmedetomidine therapy. The primary outcome was the composite of adverse events including bradycardia, hypotension, increasing vasopressor/inotrope requirements, and asystole. Secondary outcomes included individual components of the primary outcome. Patients that experienced adverse events were compared to those that did not experience adverse events to identify risk factors for adverse events. A total of 197 patients were included. There were 116 adverse events in 106 patients. Hypotension was the most common adverse event, making up 60.3% of adverse events reported. Increased vasopressor requirement and bradycardia both occurred in 22 patients (18.9%). Asystole occurred in two patients. B-type natriuretic peptide (BNP) levels were significantly higher in those experiencing an adverse event (848 pg/mL vs. 431 pg/mL; P = 0.03). Conclusions: Patients admitted to the CICU experienced a high rate of adverse events with dexmedetomidine use. Those experiencing adverse events were more likely to have a higher BNP. Future studies should explore the safety of alternative sedative agents to ascertain safe pharmacological options for patients admitted to the CICU.